SIFAT KIMIA DAN KUALITAS ARANG LIMA JENIS KAYU ASAL KALIMANTAN BARAT - Lisna Efiyanti; Suci Aprianty Wati; Dadang Setiawan; Saepulloh; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2020)
Various wood producing tree species grows in large forest area of Indonesia. Wood could be used for variousproducts such as furniture, crafts, building constructions and other products like charcoals. Utilization of productsis also generaly associated with physical, chemical, anatomy and mechanics characteristic of wood. This research aimsto determine chemical and extractive composition of five lesser-known wood species from West Kalimantan, namelykumpang, bengkulung, sawang, kempili and ubar wood, and their influences on charcoal properties produced fromcorresponding wood types. The chemical and extractive components of the five wood types were analyzed accordingto the Indonesian National Standard (SNI) method. Each wood species was heated into charcoal through pyrolysismethod with a temperature of 500°C for 4 hours. Results show that the cellulose, pentosan, lignin of these five woodspecies are 51.53−61.16%; 13.93−17.67%; and 26.55−38.46% respectively. The solubility in cold water, hotwater, NaOH 1% and alcohol-benzene are ranged from 0.632−2.640%; 3.28−8.41%; 10.41−19.01%; and3.38−4.3% respectively. Water, ash and silica contents from these woods are respectively ranged from 7.97−9.97%;0.32−2.14%; and 0.21−0.68%. The charcoal products were obtained from five wood types generally have fulfilled theIndonesian National Standard (SNI) requirements with the value of water, ash, volatile matter and carbon contentsare ranged from 0.01−0.69%; 0.59−5.40; 13.95−26.15%; and 73.05−84% respectively. The best quality ofcharcoal was obtained from kumpang wood charcoal.